Analisa Perhitungan Susut Daya Dan Energi Dengan Pendekatan Kurva Beban Pada Jaringan Distribusi PT. PLN (Persero) Area Pekanbaru - S, Donald Alfredo; Ervianto, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Loss of power caused by the presence of conductive permanent resistance. Ideal conductor should not have resistance, but in fact every object has a resistance to electric. Therefore it is necessary for the calculation of power and energy losses generated by the conductor. Power and energy losses calculation is performed on the primary distribution system, namely when the system load. Loss of the total power generated in this research amounted to 69 703, 304 Watt and percentage power losses of the average load is equal to 1.273%, while energy losses of 50186.4 kWH and percentage of energy losses equal to 1.273%.Keywords : Loss of power, Loss of energy, the primary distribution system